On the transference of the mantids collection (Insecta, Mantodea) from the Entomological Collection of Instituto Butantan to the Museu Nacional, Rio de Janeiro, Brazil - Ferraz, Bernardo; Souza-Dias, Pedro; Virginio, Flávia (EntomoBrasilis, 2021)
Brazil is one of the most diverse countries in the world, hosting more than 250 known species of mantids (Mantodea). Studying natural history collections is crucial to identify, describe new taxa and solve taxonomic issues, improving the knowledge about the biodiversity. Here we document the transference of the mantids collection from the Entomological Collection of Instituto Butantan (São Paulo, Brazil) to the Museu Nacional (Rio de Janeiro, Brazil) and provide a morphological assessment on the 33 transferred mantids. We recognized 13 genera and 12 species, with diversified distribution in Brazil, although 6 specimens from 4 genera could not be identified at a specific level. The transference of this collection starts a new phase of restructuration and recognition of the Medical Entomology scope of the donor collection, aside from helping the rebuilt of the Entomological Collection of the Museu Nacional, lost in the 2018 fire, and allowing further researches within the group.